KARAKTERISTIK TEPUNG KOMPOSIT YANG DISUPLEMENTASI RUMPUT LAUT SEBAGAI BAHAN BAKU PRODUK KULINER - . Kartiwan; Zulianatul Hidayah; Bachtaruddin Badewi (Politeknik Pertanian Negeri Kupang, 2009)
Composite Flour Characteristics At Suplementasi Sea Grass Upon Which Standard Kuliner Product. The experiment was conducted at Food Technology Laboratory Politani Negeri Kupang lasted on April to November 2008. The objectiveresearch to produced good quality composite flours to prepare data base for produce excellent quality culinary product. The experiment used RCBD and 3 replications. The treatments were six flour formulas base on wheat and indigenous flour (K1 up to K6 added by indigenous flours 15%, 30%, 45%, 60%, 75% and 90% respectively). The indigenous flours were combination from waxy corn, sorghum,sweet potatoes, and seaweed. The variables observed were water absorption, gelatination, liquid viscosity, pulp thickness, expansion of dough. Data were analised using Anova and DMRT.The gelatination temperature and water absorption were increased at composite flours with high indigenous flour contents. Viscocity and the dough expansion of composite flour decreased with high indigenous flour contents. The pulp thickness of composite flours as same as character with liquid viscosity.Keywords: composite flours, supplementation, seaweed, culinar